Strategically Speaking English: Upgrading Public Speaking Skills through Strategy Training in High Schools - Febti Ismiatun; Dzurriyyatun Ni’mah; Fitri Awaliyatush Sholihah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This article describes planning, implementation, and long-term strategies of a community service project and aims to help high school students become more proficient public speakers. The first step of the preparation process was determining the needs of the students through preliminary surveys. Next, a WhatsApp group was created for coordination, and Zoom meetings were held to address the difficulties that the students were having with English public speaking. The main problems that were found were pessimism, fear of making mistakes, articulation difficulties, and lack of confidence. To solve these problems, training materials including the basic theory of public speaking, speaking techniques, real-world exercises, and self-evaluation were created. Videos and PowerPoint presentations were also included in both onsite and online training. The program's execution comprised eight sessions where students learned about different public speaking techniques, put them into practice, and got feedback. Strategies for sustainability, including ongoing teacher training, frequent workshops, the creation of accessible learning modules, the establishment of public speaking groups, and recurring evaluations, were suggested to guarantee the program's long-term impact. The project effectively increased students' self-assurance and public speaking abilities, and continued and increased training efforts.To format your abstract, use the Microsoft Word template style.